The Application of Integrated Multi Trophic Aquaculture (IMTA) Using Stratified Double Net Rounded Cage (SDFNC) for Aquaculture Sustainability - Sapto P. Putro; Widowati Widowati; Suhartana Suhartana; Fuad Muhammad (International Journal of Science and Engineering, 2015)
The increase of fishery production nationally and internationally may impact on the potential emergence of a variety of environmental problems. The application of sustainable aquaculture is urgently needed by breeding fish for commercial purposes in a manner such that it has a minimum impact on the environment, contributing to the development of local communities and generating economic benefits. The design of the cage and farming practice in aquaculture activities are the important steps to ensure that farming activity is still observed in order to anticipate the risk of organic enrichment caused by the activities. The application of Integrated Multi-Trophic Aquaculture  (IMTA) on the Stratified Double Floating Net Cage  (SDFNC) integrated with biomonitoring are an appropriate solution to the ongoing productive farming practices. IMTA is an aquaculture practice using more than one species of biotas which have ecologically mutual relationship as a part of the food chain in the area at the same time. The application of IMTA allows farmers to get several aquaculture products in the same area without increasing the horizontal area of the farms. At first, the SDFNC has been applied for farming Cyprinus carpio and Tilapia niloticus as polyculture system in freshwater ecosystem of Rawapening Lake, Central Java. Its operation has been able to increase the production capacity of at least 75% of conventional cages. The application of SDFNC-IMTA using milkfish (Chanos Chanos), seaweed (Kappaphycus alvarezii), and white shrimp (Litopenaeus vannamei) has been able to minimize the impact and maintain the water ecosystem in the Gulf Awerange, South Sulawesi.